Uso de modelos lineares mistos na avaliação genética de escores visuais: estudo de simulação - Duitama, L.o.; Farah, M.m.; Utsunomiya, A.t.h.; Ono, R.k.; Pires, M.p.; Fonseca, R. (Universidade Federal de Minas Gerais, Escola de Veterinária, 2014)
This study aimed to evaluate the application of linear mixed models methodology using simulated data for trait visual scores, two population structures (with and without selection), two levels of heritability (0.1 and 0.4) and four levels of connectability (8, 20, 38 and 60%) were examined. Populations with and without selection consisted of 6,660 and 3,360 animals respectively, of which, the last in 2460 had score visual phenotypes. The scores were simulated with an underlying normal distribution from which intervals were defined corresponding to each category of the visual scores. The simulation process was performed in software R, to estimate genetic parameters and predict breeding values through software Wombat using animal model, considering models with and without fixed effects. The evaluation criteria were: the mean squared error (EQM) for heritability and Spearman correlations between true and predicted breeding values. Estimates of heritability showed close to the true value in scenarios without selection (0.084-0.101 and 0.367-0.389), however when selection was applied heritability was underestimated (0.032 and 0.278). Consistent with heritability, the correlations were higher for the scenarios without selection and with heritability of 0.4 (0.86-0.89). In all scenarios simulated the inclusion of fixed effects in the model improved the estimates of heritability and correlations between true and predicted breeding values. The level of connectability affected the correction of fixed effects done by allocating visual scores. The linear mixed model methodology can be used in the estimation of genetic parameters and predicted breeding values for visual scores in populations without selection, however, is not suiting in populations under selection.

Objetivou-se avaliar a aplicação da metodologia de modelos lineares mistos em características de escores visuais por meio de simulação, considerando-se duas estruturas populacionais (com e sem seleção), dois níveis de herdabilidade (0,1 e 0,4) e quatro níveis de conectabilidade (8, 20, 38 e 60%). As populações com e sem seleção estavam constituídas por 6660 e 3360 animais, respectivamente, dos quais os últimos 2460 animais tinham fenótipo para o escore visual. Assumiu-se uma variável contínua adjacente ao escore visual, a partir da qual foram definidos os intervalos correspondentes a cada categoria de escore visual. O processo de simulação foi feito por meio do software R, e a estimação de parâmetros e predição de valores genéticos pelo software Wombat, sob modelo animal, considerando-se modelos com e sem efeitos fixos. Os critérios de avaliação foram: o erro quadrático médio (EQM) para a herdabilidade e as correlações de Spearman entre os valores genéticos verdadeiros e preditos. As estimativas da herdabilidade apresentaram-se próximas do valor verdadeiro nos cenários sem seleção (0,084-0,101 e 0,367-0,389), no entanto este resultado não ocorreu quando houve seleção, pois a herdabilidade apresentou-se subestimada (0,032 e 0,278). As correlações apresentaram-se maiores nos cenários sem seleção e com herdabilidade de 0,4 (0,86-0,89). Em todos os cenários simulados, a inclusão do efeito fixo no modelo melhorou as estimativas de herdabilidade e as correlações entre os valores genéticos verdadeiros e preditos. O nível de conectabilidade afetou a correção dos efeitos fixos feita pela atribuição dos escores. Em conclusão, a metodologia dos modelos lineares mistos pode ser utilizada na estimação de parâmetros e predição de valores genéticos de escores visuais em populações sem seleção, entretanto não se apresenta adequada em populações sob seleção.
Using linear mixed models in genetic evaluation of visual scores: simulation study
Keywords: gado de corte; parâmetros genéticos; software R; beef cattle; genetic parameters; software R